Geographic variation in long-term health outcomes following myocardial infarction in England - Charlotte Sturley; Tamara del Toro; Jonathan A Batty; Eleanor Booth; Marlous Hall (Heart, 2026)
Background Nationwide studies report the high incidence of major health outcomes following myocardial infarction (MI). This cohort study investigates variation in incidence of health outcomes following MI between health commissioning areas within England. Methods All adults ≥18 years of age with index MI admitted to hospital within all 106 integrated care board (ICB) subpopulations in England were included (2008–2017). The cumulative incidence of all-cause mortality and non-fatal health outcomes (subsequent MI and first hospitalisation for heart failure, atrial fibrillation, cerebrovascular disease, peripheral arterial disease, severe bleeding, renal failure, diabetes mellitus and depression) within 9 years of follow-up was calculated from flexible parametric survival models adjusted for age, sex, year of MI and deprivation. Choropleth maps and funnel plots were used to visualise the degree of variation in incidence of outcomes by ICB subpopulation. The intraclass correlation coefficient (ICC) was used to determine the degree of variation explained at the area versus patient level. Results A total of 381 518 individuals with MI (n=2 807 195 hospital admissions) were included in the study. The crude incidence of post-MI health outcomes varied between areas, including heart failure (range 20.2%–47.9%), severe bleeding (14.3%–34.6%), renal failure (23.7%–38.0%) and all-cause mortality (34.3%–47.7%). The incidence of each major health outcome following MI fell within expected range (between 95% control limits) after adjusting for patient demographics with the exception of two sub-ICBs in Lancashire and South Cumbria, where rates were higher than expected. Overall, variation observed was predominantly explained by region-specific patient demographic profiles rather than at the ICB subpopulation level (ICC